Evaluation of the first year of the Oxpal Medlink: A web-based partnership designed to address specific challenges facing medical education in the occupied Palestinian territories. (3rd February 2014) - Penfold, Rose S; Ali, Mohammad A; Ali, Adam M; Patel, Ishita; MacGregor, Thomas; Shankar, Sushma; Cahill, Thomas J; Finlayson, Alexander ET; Mahmud, Imran
Objectives: To (1) evaluate educational needs of clinical students at Al-Quds University Medical School in the West Bank; (2) address these needs where possible using synchronous distance learning, with clinicians in Oxford providing case-based tutorials to undergraduates in the West Bank via an online platform (WizIQ) and (3) assess the impact of this education. Design: Review of online OxPal Medlink database for tutorials held between March 2012 and April 2013. Needs assessment and evaluation of student and tutor experiences through online questionnaires, focus groups and semi-structured interviews. Setting: Oxford University Hospitals, Oxford, UK, and Al-Quds University Medical School, Abu Dies, Palestine. Participants: Doctors at Oxford University Hospitals and fourth-, fifth- and sixth-year medical students and faculty members at Al-Quds Medical School. Main outcome measures: Number of tutorials, student participation, student-rated satisfaction and qualitative feedback from tutors and students. Results: Students demonstrated strong theoretical knowledge but struggled to apply this in presentation-based scenarios. Between March 2012 and April 2013, 90 tutorials were delivered to 60 students. Feedback: >95% respondents rated tutorials as 'Excellent' or 'Good' and 'Very' or 'Fairly' relevant to their future practice in Palestine. Students reported the programme had modified their approach to patients but requested better synchronization with concurrent attachments and clarification of learning outcomes. Conclusions: OxPal Medlink is a novel, web-based distance-learning partnership designed to overcome some of the challenges to local medical education in the occupied Palestinian territories. Evaluation of the first year indicates teaching is relevant to local practice and of high quality. This approach may have the potential to strengthen local capacity for medical education.